Water Quality From Gualaxo Do Norte And Carmo Rivers (Minas Gerais, Brazil) After The Fundão Dam Failure - Nogueira, Leonardo Brandão; Sousa, Sabriny Melo; Santos, Camila Gonçalves Lobo; Araújo, Gustavo Simões; Oliveira, Laser; Nogueira, Katiane Oliveira Pinto Coelho (Anuário do Instituto de Geociências, 2021)
Mining waste is rich in trace elements, which present a high toxic potential and may represent a risk for aquatic ecosystems. The Fundão dam failure, considered the largest environmental disaster in the world, affected 663.2 km of watercourses, including Carmo and Gualaxo do Norte Rivers. The ore tail also affected the riverside communities, destroying villages, killing people and affecting the subsistence farming. To evaluate the influence of the mine tailing wave on the water quality of the Carmo and Gualaxo do Norte Rivers water samples were collected at nine points located in Barra Longa during the rainy season. Physicochemical parameters (conductivity, resistivity, EH, total dissolved solids, pH and temperature) and major, minor and trace elements concentrations (Ba, Co, Cr, Cu, Ni, Sc, Sr, V, Zn, As, Pb, Al, Fe, Mn, Ca, K, Mg and P) were evaluated and compared with previous studies and conformity limits established by a national resolution (CONAMA Resolution N°357/2005). Only conductivity, Fe and Mn presented non-conformity values according to CONAMA Resolution N°357/2005. These results may be related not only to the dam burst but also to the rainy season and non-detectable pollution sources. Furthermore, the decreased levels in the toxic elements in the rivers over time, may be related to its association with sediments in addition to their flux to the Atlantic Ocean. Thus, after nearly six years, the environmental and social impacts are still alive and the minerals dragged to the riverbed could bring cumulative effects for the entire environment what means an uncertain future to the Rio Doce Basin and adjacent coastal zone.